2010
DOI: 10.1111/j.1526-4637.2010.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Orofacial Pain: A Survey of General Dentists in German University Hospitals

Abstract: The prevalence of COP is 5% in German University dental practices, where current guidelines of COP treatment are followed incompletely, and patients with psychological disorders are usually not treated. Interdisciplinary practice principles should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
(85 reference statements)
1
24
0
3
Order By: Relevance
“…Up to a quarter of the population reports OFP (excluding dental pain), and up to 11 % of this is chronic pain. Patients with OFP present to a variety of clinicians because it is associated with significant morbidity and high levels of health care utilization (Aggarwal et al 2006;Bell et al 2008;Benoliel et al 2008;Wirz et al 2010;Zakrzewska and Hamlyn 1999). Severe OFP often is diagnosed as trigeminal neuralgia, with little distinction made between typical or atypical types.…”
Section: Painsmentioning
confidence: 98%
“…Up to a quarter of the population reports OFP (excluding dental pain), and up to 11 % of this is chronic pain. Patients with OFP present to a variety of clinicians because it is associated with significant morbidity and high levels of health care utilization (Aggarwal et al 2006;Bell et al 2008;Benoliel et al 2008;Wirz et al 2010;Zakrzewska and Hamlyn 1999). Severe OFP often is diagnosed as trigeminal neuralgia, with little distinction made between typical or atypical types.…”
Section: Painsmentioning
confidence: 98%
“…19 Studies in a German secondary care sector have shown inadequate management 9 and similar findings have been reported in the United Kingdom. 28 A qualitative study of doctors, dentists, and patients in the United Kingdom showed that current management of PIFP was ineffective and unsatisfactory from everyone's perspective.…”
Section: Overall Managementmentioning
confidence: 51%
“…8 A review of 97 patients with facial pain attending a neurologic tertiary center in Austria classified 21% as having PIFP. 9 In a UK community-based study, chronic orofacial pain was identified in 7% of the population and these patients often have other unexplained symptoms, such as chronic widespread pain, irritable bowel syndrome, and chronic fatigue, and show high levels of health anxiety, reassuranceseeking behavior, and recent adverse events. 10 …”
Section: Epidemiologymentioning
confidence: 99%
“…Pain is described as deep, diffuse, continuous and persistent and may present sensation of burning or pressure. Pain may be started by an invasive dental treatment or surgery [42][43][44] . Eagle's syndrome is a disease affecting styloid processes, which are extensions of the temporal bone with length varying from 15 to 30 millimeters.…”
Section: Discussionmentioning
confidence: 99%